Space-based retrieval of NO 2 over biomass burning regions: quantifying and reducing uncertainties - N. Bousserez (Atmospheric Measurement Techniques, 2014)
The accuracy of space-based nitrogen dioxide (NO 2 ) retrievals from solar backscatter radiances critically depends on a priori knowledge of the vertical profiles of NO 2 and aerosol optical properties. This information is used to calculate an air mass factor (AMF), which accounts for atmospheric scattering and is used to convert the measured line-of-sight "slant" columns into vertical columns. In this study we investigate the impact of biomass burning emissions on the AMF in order to quantify NO 2 retrieval errors in the Ozone Monitoring Instrument (OMI) products over these sources. Sensitivity analyses are conducted using the Linearized Discrete Ordinate Radiative Transfer (LIDORT) model. The NO 2 and aerosol profiles are obtained from a 3-D chemistry-transport model (GEOS-Chem), which uses the Fire Locating and Monitoring of Burning Emissions (FLAMBE) daily biomass burning emission inventory. Aircraft in situ data collected during two field campaigns, the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) and the Dust and Biomass-burning Experiment (DABEX), are used to evaluate the modeled aerosol optical properties and NO 2 profiles over Canadian boreal fires and West African savanna fires, respectively. Over both domains, the effect of biomass burning emissions on the AMF through the modified NO 2 shape factor can be as high as −60%. A sensitivity analysis also revealed that the effect of aerosol and shape factor perturbations on the AMF is very sensitive to surface reflectance and clouds. As an illustration, the aerosol correction can range from −20 to +100% for different surface reflectances, while the shape factor correction varies from −70 to −20%. Although previous studies have shown that in clear-sky conditions the effect of aerosols on the AMF was in part implicitly accounted for by the modified cloud parameters, here it is suggested that when clouds are present above a surface layer of scattering aerosols, an explicit aerosol correction would be beneficial to ...